Paraelectric properties of PbTe doped with Ga - Tetyorkin, V.; Movchan, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The static dielectric constant was investigated as a function of temperature and carrier concentration in In(Cu)/p-PbTe Schottky contacts. Single crystals of PbTe doped with Ga were used as substrates for preparation of the contacts. The static dielectric constant was found to obey the Curie-Weiss law with the negative Curie temperature for all samples investigated including those ones with the lowest values of the hole concentration. There is an evidence that the Curie temperature is dependent on the compensation state in doped PbTe. The increase of the compensation results in nonmonotonous dependence of the Curie temperature on carrier concentration. The effect of the foreign impurities and native defects on the static dielectric constant and Curie temperature is discussed.